New financial intermediary development indicators for developing countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Financial development indicators are often applied to countries/regions without taking into account specific financial development realities. Financial depth in the perspective of monetary base is not equal to liquid liabilities in every development context. This paper introduces complementary indicators to the existing Financial Development and Structure Database (FDSD) and unites two streams of research. It contributes at the same time to the macroeconomic literature on measuring financial development and responds to the growing field of economic development by means of informal financial sector promotion and microfinance. The paper suggests a practicable way to disentangle the effects of the various financial sectors on economic developments.
Keywords: E00; E26; 330; Finance; Development; Formalization; Panel; Developing Countries